Marketing Management Product Marketing Strategy Against Covid 19 - Chenthasili, Semlith (Scieclouds Publishing, 2023)
This article discusses product marketing strategies during the Covid 19 period. The crisis that occurred during the ongoing Covid 19 pandemic has put pressure on SME businessmen to continue to survive. There are some businesses that are improving, while others are struggling for just a sale or two. The purpose of this article is to know the purpose of marketing, know the purpose of the product, know the intent of the marketing strategy, know what Covid 19 is, and hopefully be able to provide solutions related to product marketing problems affected by Covid 19.